FAKTOR-FAKTOR YANG MEMPENGARUHI INTENSI NASABAH BERINFAK PADA BSI MOBILE - Faishal Daudshah (2022)
Mobile banking services increasing Infak fundraising through BSI Mobile can be triggered in a variety of factors. The aim of this study is to integrate the TAM theory and the construct of religiosity to examine customer intentions to use infak services in BSI Mobile. This study used quantitative approach methods with 100 population, consisting of customers of Bank Syariah Indonesia (BSI) collected from South Jakarta City. The data obtained is primary data processed through SmartPLS software with analytical techniques using the Partial Least Square method. The result of this study is that the perceived usefulness has a significant influence on behavioral intentions. The perceived ease of use has an insignificant influence on behavioral intentions. Religiosity has an insignificant influence on behavioral intentions. The perceived usefulness is a factor that influences the behavioral intention of customer infak towards BSI mobile banking. Policymakers need to have an agenda or activity that discusses more deeply about the benefits of infak especially through BSI Mobile service. To increase customer awareness of the benefits of infak. The limitation of this study is that it only uses 3 free variables and the scope of the study is only in the City of South Jakarta.